Plasmodium vivax and SARS-CoV-2 co-infection in Venezuelan pregnant women: a case series - Fhabián S. Carrión-Nessi; Daniela L. Mendoza-Millán; Óscar D. Omaña-Ávila; Sinibaldo R. Romero; Augusto Moncada-Ortega; Mary Lopez-Perez; Jaime R. Torres; Óscar Noya-González; David A. Forero-Peña (Malaria Journal, 2023)
Abstract Background Malaria‐endemic areas are not spared from the impact of coronavirus disease 2019 (COVID-19), leading to co-infection scenarios where overlapping symptoms impose serious diagnostic challenges. Current knowledge on Plasmodium spp. and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) co‐infection in pregnant women remains limited, especially in Latin America, where Plasmodium vivax infection is highly prevalent. Methods This is a case series of five pregnant women with P. vivax and SARS-CoV-2 co-infection hospitalized in two main malaria referral centers of the Capital District and Bolivar state, Venezuela between March 13, 2020 and December 31, 2021. Results Clinical and laboratory data from five pregnant women with a mean age of 22 years were analyzed; three of them were in the third trimester of pregnancy. Comorbidities included obesity in two cases, hypertension in one, and asthma in one. Three out of five patients had severe to critical COVID-19 disease. Dry cough, fever, chills, and headache were the most frequent symptoms reported. Laboratory analyses showed elevated aspartate/alanine aminotransferase and creatinine levels, thrombocytopenia, and severe anemia as the most relevant abnormalities. The mean period between symptom onset and a positive molecular test for SARS-CoV-2 infection or positive microscopy for Plasmodium spp. was 4.8 ± 2.5 days and 2.8 ± 1.6 days, respectively. The mean hospital stay was 5.4 ± 7 days. Three women recovered and were discharged from the hospital. Two women died, one from cerebral malaria and one from respiratory failure. Three adverse fetal outcomes were registered, two miscarriages and one stillbirth. Conclusion This study documented a predominance of severe/critical COVID-19 disease and a high proportion of adverse maternal–fetal outcomes among pregnant women with malaria and COVID-19 co-infection. More comprehensive prospective cohort studies are warranted to explore the risk factors, management challenges, and clinical outcomes of pregnant women with this co-infection.